Improving Resilience and Self-Esteem among University Students with Entrepreneurship Simulation Board Game - Kususanto Prihadi; Damien Z.Y. Cheow; Jonathan H.E Yong; Megaaneesh Sundrasagran (Institute of Advanced Engineering and Science, 2018)
This study aims to evaluate the effect of the frequency of playing a board game that simulates entrepreneurial experience called “Traders” on the university students’ resilience and self-esteem. Traders Board Game (TBG) was developed in 2015 with an aim to improve several entrepreneurship skills among young adults, and resilience being one of them. Pre and posttests of resilience have been done to 12 participants before they were divided into three groups: the control group, who did not play the game, the experimental group A, who played the game once a week for three weeks, and the experimental group B, who played the game twice a week for three weeks. Resilience was measured by adapting Connor-Davidson Resilience Scale, whereas self-esteem was measured by utilizing Mruk two-dimensional Self-esteem scale. There was a statistically significant difference among the the three groups in resilience improvement, where the experimental group A scored the highest, and no significant difference was discovered in terms of self-eteem improvement. The results suggested that playing TBG in certain frequency significantly improves resilience among the participants.